PENERAPAN MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Intan Cahyani; Syamsuryani Eka Putri Atjo; Siti Raihan (STKIP Subang, 2026)
This study aims to improve students' creative thinking skills through the application of the inquiry learning model in science and social studies learning for fifth-grade elementary school students. The research employed a Classroom Action Research (CAR) method using the Kemmis and Taggart model, which consists of four stages: planning, implementation, observation, and reflection. The study was conducted in two cycles, each consisting of two meetings. The research subjects were 15 fifth-grade students at SD Negeri 55 Padang Lambe, Palopo City. Data collection techniques included observation and written tests. Data analysis was performed using descriptive quantitative and qualitative methods. The results showed that the application of the inquiry learning model improved students' creative thinking skills, as evidenced by increased activeness in asking questions, discussing, and expressing ideas. Teacher activity increased from 61.1% in cycle I to 88.9% in cycle II, student activity increased from 41.6% in cycle I to 83% in cycle II, and learning mastery increased from 33.3% in cycle I to 80% in cycle II. Students' creative thinking skills developed in the aspects of fluency (from 65% to 85%), flexibility (from 60% to 82%), originality (from 58% to 80%), and elaboration (from 62% to 83%). The learning process also became more interactive, meaningful, and student-centered. Thus, it can be concluded that the application of the inquiry learning model is effective in improving students' creative thinking skills in science and social studies learning for fifth-grade elementary school students.